Assessing the provenance of Poverty Point copper through LA-ICP-MS compositional analysis. (April 2016) - Hill, Mark A.; Greenlee, Diana M.; Neff, Hector
Abstract: The Poverty Point site is the largest and most complex Archaic period earthwork site in eastern North America and the type site of the Poverty Point culture. Poverty Point holds a prominent position in eastern North American prehistory in part due to the extensive exchange system—the first of such scale—that brought exotic materials to this site from the Appalachians, Ohio Valley, and Upper Mississippi Valley. Among these exotic materials, copper was introduced into the Poverty Point exchange system from sources often posited to reside in the upper Great Lakes region, an idea reinforced by the identification of Upper Mississippi Valley sources for galena found at the site. This study tests such an assumption by using laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) analysis of six copper artifacts from the Poverty Point site and comparing the results to source samples from the Lake Superior region, central and southern Appalachian Mountains, and Canadian Maritimes. Results indicate that these copper artifacts most likely originated in the eastern sources of the Maritimes or Appalachian Mountains, rather than the Lake Superior region as long proposed. Highlights: We used LA-ICP-MS to examine the elemental composition of six copper artifacts from the Poverty Point site in Louisiana Compositional profiles of these artifacts were compared with those of 62 copper source samples Source areas were broadly defined as Appalachian, Canadian Maritimes, and Lake Superior Results indicate a probable eastern source (Appalachians and Maritimes) for the analyzed Poverty Point copper.